2018
DOI: 10.2478/aiht-2018-69-3114
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, cholinesterase activity, and DNA damage in the liver, whole blood, and plasma of Wistar rats following a 28-day exposure to glyphosate

Abstract: In this 28 day-study, we evaluated the effects of herbicide glyphosate administered by gavage to Wistar rats at daily doses equivalent to 0.1 of the acceptable operator exposure level (AOEL), 0.5 of the consumer acceptable daily intake (ADI), 1.75 (corresponding to the chronic population-adjusted dose, cPAD), and 10 mg kg-1 body weight (bw) (corresponding to 100 times the AOEL). At the end of each treatment, the body and liver weights were measured and compared with their baseline values. DNA damage in leukocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 73 publications
1
25
0
3
Order By: Relevance
“…The decreased activities of CAT and SOD can be used to indicate the accumulation of superoxide radicals and/or hydroxyl radicals in the liver. GSH, as a nonenzymatic scavenger, can scavenge a wide variety of reactive species [38]. GSH-Px works together with CAT to scavenge excess lipid peroxide and hydrogen, which is helpful for eliminating peroxide during the reaction between GSH and H 2 O 2 [27].…”
Section: Discussionmentioning
confidence: 99%
“…The decreased activities of CAT and SOD can be used to indicate the accumulation of superoxide radicals and/or hydroxyl radicals in the liver. GSH, as a nonenzymatic scavenger, can scavenge a wide variety of reactive species [38]. GSH-Px works together with CAT to scavenge excess lipid peroxide and hydrogen, which is helpful for eliminating peroxide during the reaction between GSH and H 2 O 2 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidant-mediated responses, such as apoptotic or necrotic cell death, membrane lipid peroxidation, metabolic perturbation, and deregulation of several signaling pathways) are several well-known toxicological effects of insecticides 93,94 . Hence, the study of antioxidant enzymes has been used as a popular method to evaluate the response of multiple animal models, including rats, mice, fish, and green snake head, under pesticide-induced stress conditions 78,[95][96][97][98][99][100] . In the present study, lufenuron was found to increase the level of MDA and decrease the level of GPx and SOD enzymes in liver cells in mothers and their fetuses in a dose-dependent manner, which refers to the oxidative stress posed by the insecticide on the liver cells of the treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Data for liver and kidney weights have been more variable. For example, one report indicated decreases in liver weight (Ren et al, ), another increase in organ weights of liver, brain, kidney and heart (Cox, ; El‐Shenawy, ; Milić et al, ), and another study reported no changes in liver weight (Çağlar & Kolankaya, ). The U.S. Environmental Protection Agency (EPA) suggested that they depended on glyphosate concentration and animal species (EPA, ).…”
Section: Discussionmentioning
confidence: 99%